Kingdom of Lesotho : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Kingdom of Lesotho. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2019 Article IV Consultation highlights that while international reserves are at adequate levels and banks remain well-capitalized in the Republic of Lesotho, domestic arrears are beginning to impact the broader economy, exacerbating growth challenges posed by structural impediments. The recently passed FY2019/20 budget envisages an ambitious consolidation that could begin to lay the groundwork for a transition to private-sector driven growth. Construction related to the second phase of the Lesotho Highlands Water Project will support medium-term growth, and the diamond and textile industries have positive prospects. Fiscal adjustment is needed to address government arrears, buttress debt sustainability, and safeguard the link to the rand. Generating strong and inclusive growth will require improved public service delivery and the private sector to become the primary engine of job creation. Better targeting of the government's resources, Public Financial Management reforms, and reorienting both expenditures and the role of government in the economy will be critical to achieve these goals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet